Research on aero-engine blade surface detection based on three datum points integrating algorithm - Bin Sun; Gang Zheng; Xiongxing Zhang; Lang Bai (AIP Advances, 2020)
Aiming at the application of a 2D laser profile sensor in the detection of an aero-engine blade surface, a three-point alignment transformation algorithm based on a single-standard ball is proposed. In the algorithm, the standard ball is used to measure the coordinate conversion reference, and the three characteristic points, such as the center of the ball, the vertex, and the side extremum, are scanned by using a laser sensor once. When measuring the rotated blade, the laser sensor scans again, and the coordinate values of the three feature points in the new coordinate system are obtained through coordinate conversion technology. With these three pairs of feature points as the reference point for coordinate transformation and using a three-point alignment transformation and stitching algorithm, the 3D reconstruction of the blade profile measurement point cloud data can be accurately realized. The experimental results show that the 2D laser profile sensor can realize the on-line and fast detection of the aero-engine blade surfaces less then10 µm.